THE GROWING INTEREST IN BEHAVIORAL ECONOMICS AND ITS RELEVANCE TO CONSUMER BEHAVIOR: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
The rising interest in behavioral economics stems from its relevance in understanding consumer behavior. It explores the psychological and emotional aspects that impact decision-making, revealing insights into why individuals choose as they do and their reactions to incentives and feedback. This comprehension is vital for crafting successful strategies across diverse domains such as marketing, public policy, and environmental preservation.